Pendampingan MDTA Al-Mujahid dalam Meningkatkan Hafalan Qur`an dan Hadist melalui Media Permainan Edukatif - Yulistiana Yulistiana; Milda Kuswandi; Noer Syaqilla; Sinta Puspita; Rifka Nurzahra (BADAN PENERBIT STIEPARI PRESS, 2026)
This community service program aims to improve students’ ability to memorize the Qur’an and Hadith through the application of a service-learning approach using educational game media at MDTA Al-Mujahid, Kebonmanggu Village. The activity was motivated by students’ low memorization consistency due to conventional and less interactive learning methods. Through the service-learning approach, university students acted as facilitators in mentoring sessions that combined interactive lectures, educational games, and reflections on Islamic values. The implementation stages included initial observation, the design of learning media (memorization cards and Islamic puzzles), mentoring activities, and evaluation through reflection and feedback from teachers and students. The results showed a significant improvement in students’ learning motivation, memorization ability, and religious attitudes. Students were more enthusiastic and focused during memorization sessions due to the engaging and participatory learning atmosphere. Teachers also reported that this activity fostered a more active and innovative classroom environment. The service-learning model proved effective in building collaboration between students, teachers, and facilitators while strengthening learners’ spiritual character.